ANALISA KADAR H2S (HIDROGEN SULFIDA) DAN KELUHAN KESEHATAN SALURAN PERNAPASAN SERTA KELUHAN IRITASI MATA PADA MASYARAKAT DI KAWASAN PT. ALLEGRINDO NUSANTARA DESA URUNG PANEI KECAMATAN PURBA KABUPATEN SIMALUNGUN TAHUN 2013 - JUN EDY PAKPAHAN; wirsal hasan; indra chahaya (Lingkungan dan Kesehatan Kerja, 2014)
Development of maintenance of increasing farm fields can affect the quality of the environment, one of which is the quality of the air can be decreased because of the pollution in the farm by impact. PT. Allegrindo Nusantara is one the largest farm in North Sumatra even in Southeast Asia which is located in the village of Urung Panei sub-district Purba district Simalungun. Hydrogen sulphide is a colorless gas, are very poisonous, combustible and having the characteristics of smell of rotten eggs. This research aims to know the levels of hydrogen sulfide and respiratory health complaints and complaints of irritation of the eye on people living in the area of hog farms PT. Allegrindo Nusantara. The type of research used are descriptive in nature. The population in this research is 90 people with respondents housewife with a sample is the total sampling. The results showed that levels of hydrogen sulfide in the hog farms PT. Allegrindo Nusantara 0,0002-0,016 ppm it not exceed the level indicated in the quality raw KepMenLH No. 50 in 1996. There are 36 people (40,0%) respondents who experienced respiratory tract health complaints during the last 3 months and 27 respondents (30,0%) people who suffered eye irritation complaints during the last 3 months. The conclusion is the importance of maintaining and improving the cleanliness of the farm to prevent the smell that can cause air pollution, monitoring of the air quality on an ongoing basis. In the community, it is important to use a mask and other protective as prevention efforts against respiratory tract health complaints and complaints of eye irritation. Key Words: Hydrogen Sulfide Levels, Air Quality, Respiratory Tract Health Complaints, Complaints Of Eye Irritation.